Fat redistribution and accumulation of visceral adipose tissue predicts type 2 diabetes risk in middle-aged black South African women: a 13-year longitudinal study - Mtintsilana, Asanda (Nutr Diabetes, 2019)
BACKGROUND: Cross-sectional studies in South Africa (SA) have shown that black SA women, despite being more insulin resistant, have less visceral adipose tissue (VAT) and more subcutaneous adipose tissue (SAT) than white women. This study aimed to investigate whether baseline and/or change in body fat and its distribution predict type 2 diabetes (T2D) risk in middle-aged black SA women, 13 years later. METHODS: We studied 142 black SA women who are the caregivers of the Birth-to-Twenty plus cohort, and who had normal glucose tolerance (NGT) at baseline. At baseline and follow-up, fasting blood samples, basic anthropometry and dual-energy X-ray absorptiometry-derived body composition were measured. At follow-up, an oral glucose tolerance test was completed. The WHO diabetes diagnostic criteria were used to define NGT, impaired fasting glucose (IFG)/impaired glucose tolerance (IGT), impaired glucose metabolism (IGM) and T2D. RESULTS: At follow-up, 64% of participants remained NGT, whereas 25% developed IGM, and 11% developed T2D. The IGM and the T2D groups were combined for statistical analyses. At baseline, trunk fat mass (FM), VAT but not SAT (measures of central FM) were higher in the IGM/T2D group than the NGT group (p < 0.0001). In contrast, the IGM/T2D group had lower leg %FM at baseline than the NGT group (p < 0.0001). Baseline trunk FM (Odds ratio per 1 kg increase (95% confidence interval, 1.95 (1.43–2.67))), and VAT (OR per 10 cm(2) increase, 1.25 (1.10–1.42)), and the change in VAT (1.12 (1.03–1.23)) were associated with greater odds of developing IGM/T2D, whereas baseline leg FM (OR per 1 kg increase, 0.55 (0.41–0.73)) were associated with reduced IGM/T2D risk at follow-up (p < 0.05). CONCLUSIONS: Relative fat redistribution, with VAT accumulation, predicted the development of IGM/T2D 13 years before its onset. Prevention of central obesity is a key factor to reduce the risk of developing T2D among middle-aged urban black SA women.